Analysis and Compensation of Negative Phase-sequence for Traction Transformer - SHI Minghui; LUO Wenguang; HE Duochang; ZHANG Zhixue (Kongzhi Yu Xinxi Jishu)
It analyzed the characteristics of negative phase-sequence current for traction transformers with different connection types under different loads. The three-phase current asymmetry degree of traction transformers is serious under both traction load and feedback load. The basic theory of integrative compensation for railway static power conditioner (RPC) was introduced aiming to the power quality problems in terms of negative sequence current, reactive power and harmonic. It focused on analyzing the rating capability of RPC for eliminating the negative sequence current of three-phase to two-phase traction transformer,which could provide reference for engineering application of RPC.